COLORIMETRIC CODING AND DISTRIBUTION SYSTEM OF BIOMETRIC CHARACTERISTICS IN A PLANE LIMITED SPACE - Alexander Mikhailovich Troshkov; Vladimir Alexandrovich Ermakov; Gennadiy Vasilyevich Slyusarev (Современная наука и инновации, 2022)
The possibility of using colorimetric coding of human biometric characteristics is analyzed. A coding method and a schematic diagram of an apparatus for reading color information from a dental matrix are proposed.